Utilization of Open-Source OpenFOAM Code to Examine the Hydrodynamic Characteristics of a Linear Jet Propulsion System with or without Stator in Bollard Pull Condition. (9th December 2020) - Ghadimi, Parviz; Donyavizadeh, Negin; Taghikhani, Pouria
Abstract : With the development of high-speed crafts, new propulsion systems are introduced into the marine industry. One of the new propulsion systems is linear jet which is similar to pump jet and has a rotor, a stator, and a duct. The main difference between this system and pump jet is the placement of linear jet system under the hull body and inside a tunnel. Since this system, like a water jet, is inside the tunnel, the design idea of this system is a combination of a water jet and pump jet. In this paper, hydrodynamic performance of linear jet propulsion system is numerically investigated. To this end, the OpenFOAM software is utilized and RANS steady equations are solved using a k -ε turbulent model. The linear jet geometry is produced by assembling a Kaplan rotor, stator with a NACA 5505 cross section, and a decelerating duct. The results of numerical solution in the form of thrust, torque coefficient, and efficiency are compared with available experimental data for a ducted propeller, and good agreement is displayed. Subsequently, the hydrodynamic parameters are computed in two conditions: with a stator and without a stator. By comparing the results, it is observed that the total thrust coefficient of the propulsion system with a stator at all advance ratios increases by at least 40%. It is further observed that addition of a stator also improves its efficiency.